The complex role of post-operative magnesium on the long term serum calcium and parathyroid hormone levels in patients undergoing total and near-total thyroidectomy - Sana Viqar; Tasleem Akhtar; Nadeem Ikram; Naeem Zia (Journal of the Pakistan Medical Association, 2022)
Objectives: To assess the role of hypomagnesaemia in the development of permanent hypocalcemia following thyroidectomy. Method: The prospective cohort study was conducted from April 3, 2017, to January 2, 2020, at Surgical Unit 1, Benazir Bhutto Hospital, Rawalpindi, Pakistan, and comprised patients of either gender undergoing total and near total thyroidectomy. Post-operative calcium and magnesium levels were noted, and the patients were followed up after 6 month when fasting serum calcium, magnesium and parathyroid hormone levels were checked. Signs and symptoms of hypocalcaemia were noted. Data was analysed using SPSS 22. Results: Out of the 62 patients followed up, 57 were females (91.9%) and 5 males (8.1%). The overall mean age was 38.5 ± 12.1 years Post-operative hypomagnesaemia was seen in 6(9.8%) patients and none developed follow-up hypocalcaemia. Post-operative magnesium levels were significantly negatively correlated with follow-up parathyroid hormone level (p=0.006). Fall in magnesium post-operatively and follow-up magnesium were positively correlated with follow-up parathyroid hormone (p<0.05). Permanent hypocalcaemia was seen in 7(11.4%) patients and it was significantly associated with pre-operative and post-operative calcium levels, post-operative symptoms of hypocalcaemia and readmission for hypocalcaemia after discharge (p<0.05). Follow-up hypomagnesaemia was significantly associated with follow-up hypocalcaemia (p=0.024) and follow-up symptoms of hypocalcaemia (p=0.031). Conclusion: Acute development of mild hypomagnesaemia post-operatively may be beneficial in early positive feedback for parathyroid hormone secretion. Key Words: Magnesium, Calcium, PTH, Thyroidectomy, Post-operative, Follow-up hypomagnesaemia, Permanent hypocalcaemia.